Qualques reflexions sul principi poetic e la temporalitat liura dins Sonets barròcs enta Iseut - Laurent Alibert (Lengas)
Sonèts barròcs enta Iseut (1979) shows Pierre Bec as a poet elaborating his creation upon a background of references to the medieval literature - main object of Pierre Bec’s researches as a scholar. Rewriting the myth of Yseult in order to create a poetic work at the same time modern and freed from temporality is one of the main specific features of the Sonèts barròcs enta Iseut. If the book is freed from temporality, this is never with the aim of recreating an ersatz of Middle Ages. The analysis of some poems in this paper suggests that the connection between the medieval reference and the poetical language is made around the death and resurrection of the Occitan language : as Iseut (Yseult) seems to die and be reborn, the lost language comes back again, in a new shape, both alike and different.